Trachyscorpia cristulata Sebastolobinae ... - Ditty, James G.; Malca, Estrella; Vásquez-Yeomans, Lourdes (Zenodo, 2024)
Trachyscorpia cristulata and Phenacoscorpius nebris Early life stages of deep-water members of Idiastion kyphos Eschmeyer, 1965, Neomerinthe spp., Phenacoscorpius nebris Eschmeyer, 1965 (Scorpaeninae), Setarches guentheri Johnson, 1862 (Setarchinae), and Trachyscorpia cristulata (Goode & Bean, 1896) (Sebastolobinae), included in Sebastinae by Hardy (2005), have not been described, to our knowledge. While a visiting scientist at the Smithsonian Institution (NMNH), the senior author examined the smallest available specimen of T. cristulata (32.0 mm SL; USNM 72979; collected 14 February 1902 off Key West, Florida) and P. nebris (40.0 mm SL; USNM 422671; collected 24 May 2013 off Curacao); small juveniles of the other aforementioned taxa were not available in NMNH collections for examination. Our intent was to generate a suite of characteristics to enable recognition and discrimination of late postflexion and transforming larvae of T. cristulata and P. nebris from other scorpaenids in the WNA. Trachyscorpia ... : Published as part of Ditty, James G., Malca, Estrella & Vásquez-Yeomans, Lourdes, 2024, The lionfishes: Comparative development of Pterois volitans, Dendrochirus barberi, and D. hemprichi (Scorpaeniformes: Scorpaenidae: Pteroinae) and discrimination of their early life stages from non-pteroine scorpaenid genera in the Western North Atlantic, pp. 1-41 in Zootaxa 5446 (1) on pages 21-22, DOI: 10.11646/zootaxa.5446.1.1, http://zenodo.org/record/11084543 ...